Taking Catie - Hardt, Helen (Hardt, Helen. Temptation saga, 2016)
Catie Bay's crush on Chad McCray stretches back to her high school years, but now that she's all grown up and back from Europe, Chad is the one who's pursuing Catie, leaving both to decide what they want from each other and for the future.